Menilik Budaya Carok pada Masyarakat Madura dalam Sistem Hukum Adat di Indonesia - Sendy Pratama Firdaus; Muhammad Ghifari Fardhana Bahar; Basri Muhammad Ridwan Sangadji (Jurnal Hukum Lex Generalis, 2021)
Madurese tend to use Carok in dispute resolution. According to the Madurese community, the Carok route is the fulfillment of a sense of justice. The disputes that were resolved in Carok took the form of adultery, insult, and revenge. The practice of Carok itself is carried out by fighting between Madurese men using sickle weapons. This paper describes the value of justice according to the Madurese community, steps to prevent Carok violence, and reconceptualization of the Carok culture itself. In addition, at the end of this paper will provide a comparison with other cultures, namely, sigajeng laleng lipa which has similarities to the Carok culture to provide a reinterpretation of the Carok culture with the aim of reducing retaliation or revenge.